KESENJANGAN KETENTUAN PERNIKAHAN DI BAWAH UMUR ANTARA FIKIH MUNAKAHAT DAN UU NO. 1 TAHUN 1974 TENTANG PERKAWINAN - Halim, Abd.; Hamsin, Muhammad Khaeruddin (Al-Mazaahib: Jurnal Perbandingan Hukum, 2017)
Since the Dutch Government has divided the Dutch East Indies into three groups, namely the European and the ecquivalent to European, the Indigenous and the Far Eastern groups, since then the Civil Law applies to different classes. In the field of marriage, for example, each group has its own marital law. So the law of marriage prevailing in society is pluralistic. As a result, the gap between the legal system can not be avoided. The Marriage Act was born as an attempt to minimize the legal gap, but in reality, even though it has been in force for about three decades of legal gap in the field of marriage, there are still many of them being minors. This paper aims to explain why there is still a gap between the provisions of the underage marriage in Fikih Munakahat and the UUP and offer resolution resolution using LM's legal system theory. Friedman, an alternative policy introduced by Soetandyo Wignjosoebroto and the law of harmonization introduced by L.M. Gandhi.